Impact of Antioxidant Supplementation on Sperm Quality and Embryo Development - Salma Sadia, Waqas Iqbal, Muhammad Shakil Sadiq, Amrat Ijaz, Ahmad Farzad Qureshi, Zobia Mushtaq , Farah Naz Tahir, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Oxidative stress is a significant contributor to male infertility, adversely affecting sperm qualityand embryo development. This double-blind, randomized controlled trial aimed to evaluate theimpact of a specific antioxidant supplementation